Professional Development Schools: Preservice Candidates’ Learning and Sources of Knowledge - Duquette, Cheryll; Cook, Sharon Anne (Alberta Journal of Educational Research, 1999)
The purpose of this study was to explore the experiential learning of preservice candidates when they are involved in professional development schools and in conventional practice teaching placements. It was found that the lessons they believed they learned were categorized into four groups: curriculum planning and evaluation, pupils and pupil-teacher interactions, discipline and classroom management, and professional knowledge. Their stated sources of knowledge were personal reflections, mentor teachers, other teachers, professors, and other supportive people. Student teachers in professional development schools also learned through weekly seminars and discussion with their peers.